The writing around as a cooperative learning strategy to develop efl basic writing skills amongst tenth-grade students at Pio Jaramillo high school. academic period 2014 – 2015 - Vinces Vinces, Rosa Cecibel (2016)
The present investigation was focused on Writing Around as a cooperative learning strategy to develop EFL basic writing skills amongst tenth-grade students at Pio Jaramillo high school. Academic period 2014-2015 with a population of 30 tenth grade students. An intervention plan established for eight weeks using the Writing Around. The methods used were: scientific, descriptive, analytic, and statistic, which were useful in this research. The techniques used were tests and questionnaires. Observation sheets were used to evidence the students‟ progress. The posttest results showed the improvement of writing skills using the Writing Around strategy, and the answers gotten with the post questionnaire confirmed the influence that this strategy had on students‟ writing development. It might be concluded that students could reduce their difficulties on writing skills working with strategies that belong to cooperative learning method. A recommendation for future researchers is to insert cooperative leaning strategies to develop students‟ writing.